Gametogenesis in malaria parasites is mediated by the cGMP-dependent protein kinase. - Louisa McRobert; Cathy J Taylor; Wensheng Deng; Quinton L Fivelman; Ross M Cummings; Spencer D Polley; Oliver Billker; David A Baker (PLoS Biology)
Malaria parasite transmission requires differentiation of male and female gametocytes into gametes within a mosquito following a blood meal. A mosquito-derived molecule, xanthurenic acid (XA), can trigger gametogenesis, but the signalling events controlling this process in the human malaria parasite Plasmodium falciparum remain unknown. A role for cGMP was revealed by our observation that zaprinast (an inhibitor of phosphodiesterases that hydrolyse cGMP) stimulates gametogenesis in the absence of XA. Using cGMP-dependent protein kinase (PKG) inhibitors in conjunction with transgenic parasites expressing an inhibitor-insensitive mutant PKG enzyme, we demonstrate that PKG is essential for XA- and zaprinast-induced gametogenesis. Furthermore, we show that intracellular calcium (Ca2+) is required for differentiation and acts downstream of or in parallel with PKG activation. This work defines a key role for PKG in gametogenesis, elucidates the hierarchy of signalling events governing this process in P. falciparum, and demonstrates the feasibility of selective inhibition of a crucial regulator of the malaria parasite life cycle.